Study on shear behavior of reinforced coral aggregate concrete beam. Issue 11 (August 2020) - Da, Bo; Yu, Hongfa; Ma, Haiyan; Yu, Bo; Wu, Zhangyu; Guo, Jianbo
Reinforced coral aggregate concrete beam and reinforced ordinary aggregate concrete beam with different concrete type, concrete strength, and steel type were designed in this study to investigate their shear behavior. The shear behavior of reinforced coral aggregate concrete beam was tested, the failure mode and deflection behavior were studied, and the calculating model for the ultimate shear capacity ( V cs ) of reinforced coral aggregate concrete beam was proposed. Results showed that the failure mode of reinforced ordinary aggregate concrete beam and reinforced coral aggregate concrete beam were basically the same. As the concrete strength increases, the normal section cracking load ( V cr ), inclined section V cr, and V cs of reinforced coral aggregate concrete beam increased gradually. Furthermore, V cr and V cs of reinforced coral aggregate concrete beam were as follows: 316 stainless steel > common steel > zinc-chromium coated steel > new organic coated steel. For the coral aggregate concrete structure in ocean engineering, in order to prolong its service life, the use of new organic coated steel was suggested. At the same time, the influence of high-strength coral aggregate concrete and stirrup corrosion was comprehensively considered and the calculation model for the V cs of reinforced coral aggregate concrete beam was presented and was then verified.